Physical Drivers and Biogeochemical Effects of the Projected Decline of the Shelfbreak Jet in the Northwest North Atlantic Ocean - Lina Garcia‐Suarez; Katja Fennel (Journal of Advances in Modeling Earth Systems, 2024)
Abstract A solid understanding of the mechanisms behind the presently observed, rapid warming of the northwest North Atlantic Continental Shelf and their biogeochemical impacts is lacking. We hypothesize that a weakening of the Labrador Current System (LCS), especially the shelfbreak jet along the Scotian Shelf, is contributing to these changes and that the future evolution of the LCS will be key to accurate projections. Here we analyze the response of a transient simulation of the high‐resolution GFDL Climate Model 2.6 (CM2.6) which realistically simulates the regional circulation but includes only a highly simplified representation of ocean biogeochemistry. Then, we use the CM2.6 to force a medium‐complexity regional biogeochemical ocean model, the Atlantic Canada Model, to obtain projections of nutrient availability on the shelf. In the simulation, the shelfbreak jet weakens because of a reduction of the along‐shelf pressure gradient caused by a buoyancy gain of the upper water column along the shelf edge. This buoyancy gain is the result of warmer waters along the continental slope. Importantly, we find that the temperature‐based criterion used commonly to pinpoint the location of the Gulf Stream is misleading, causing an overestimation of the northward migration of the Gulf Stream. A fixed isotherm may indicate northward movement as a result of basin‐wide warming and not necessarily reflect changes in dynamics. The combination of the weakened shelfbreak jet and a lowering of nutrient concentrations in its source water reduce nutrient availability on the northwest North Atlantic shelf by one third by 2100 in the projection analyzed.